Using Real Options and Geometric Brownian Motion Methods to Evaluate Petroleum Projects in Indonesia - Jalaludin, Paiz; Nuraini, Ani; Rahman, Alrafiful (Jambura Journal of Mathematics, 2024)
There are several methods for evaluating the value of a project. The most commonly used method is the Discounted Cash Flows (DCF) method which is more practical in its use. However, the DCF method still has several weaknesses, including not paying attention to the flexibility of the manager's decision-making when the project is carried out. The Real Options method enhances this by offering more flexible and varied models. This study uses Benninga's version of the binomial method to evaluate the value of petroleum projects with the characteristics of existing companies in Indonesia. In this study, oil prices are assumed to move following the Geometric Brownian Motion (GBM) model which is commonly used in modeling the movement of a fluctuating price. In addition, the author also modifies the binomial model by including expansion options, divestment options and a combination of both. The results of this study show that the more options that managers can choose in decision-making, the greater the opportunity for the company to optimize profits and minimize losses.